Cost-effectiveness of empagliflozin for the treatment of heart failure: a systematic review - Liu, Jinyu; Liu, Dong; Gong, Xuepeng; Wei, Anhua; You, Ruxu (Frontiers in Pharmacology, 2023)
Objective: This study aims to synthesize evidence on the cost-effectiveness of empagliflozin for heart failure (HF). Methods: MEDLINE, Embase, the Cochrane Library, EconLit, CNKI, Wanfang Data and Chongqing VIP were searched to identify original articles on cost-effectiveness of empagliflozin for HF, and literature surveillance ended on 20 November 2022. The reporting quality of the included articles was determined using the Consolidated Health Economic Evaluation Reporting Standards statement. Results: Of 97 articles identified, 11 studies published from 2020 to 2022 met the inclusion criteria, and the overall quality was accepted. The studies were conducted in 8 countries (China, Japan, Korea, Singapore, Thailand, Australia, USA, and UK). This body of evidence suggested that add-on empagliflozin was cost effective for HF with reduced ejection fraction (HFrEF) patients compared to standard of care alone in all the related studies including China, Japan, Korea, Singapore, Thailand, and Australia. For HF with preserved ejection fraction (HFpEF) patients, add-on empagliflozin was cost effective in China and Australia, but not in USA and Thailand. For HF with diabetes, add-on empagliflozin was cost effective in United Kingdom. Moreover, the incremental cost-effectiveness ratios (ICER) were lower for patients with diabetes than without in subgroup analysis. In the uncertainty analysis of all included studies, the ICERs were most sensitive to the cost of empagliflozin and cardiovascular mortality, followed by the cost of the standard treatment, hazard ratio of HF hospitalization. Conclusion: add-on empagliflozin for HFrEF might be cost-effective or dominant compared with standard of care alone. However, for HFpEF patients, add-on empagliflozin might be cost-effective in China and Australian, but not cost-effective in USA and Thailand.